A multifunctional hole-transporter for high-performance TADF OLEDs and clarification of factors governing the transport property by multiscale simulation. Issue 22 (23rd May 2022) - Nagamura, Natsuo; Sasabe, Hisahiro; Sato, Hiroki; Kamata, Takahiro; Ito, Nozomi; Araki, Suguru; Abe, Shoki; Sukegawa, Yoshihito; Yokoyama, Daisuke; Kaji, Hironori; Kido, Junji
Abstract : A record-breaking efficient (EQE: 22%) and long-living (LT50 : 28 000 h@1000 nit) TADF OLED is realized by using a multifunctional hole-transporter. The factors governing the transport properties are quantitatively analyzed by multiscale simulation. Abstract : To date, a limited number of reports have been published on thermally activated delayed fluorescent (TADF) organic light-emitting devices (OLEDs) that simultaneously achieved high efficiencies and long operational lifetimes. The development of tailored-hole transporters is an effective solution because extensively used conventional hole-transport materials (HTMs), such as NPD or TAPC, are unsuitable for simultaneous realizations of high-efficiency and long-lifetime in TADF OLEDs. In this study, we developed a new four-dibenzofuran (DBF) end-capped hexaphenylbenzene (HPB)-based HTM, referred to as T4DBFHPB . Using this as the HTM, we simultaneously achieved high external quantum efficiency ( η ext = 22.0%), long operational lifetime (LT50 = 28 000 h), and low-drive voltage (3.83 V) at 1000 cd m −2 in green TADF OLEDs. Our research reveals the importance of a multifunctional HTM with (i) high triplet energy ( E T ), (ii) high glass transition temperature ( T g ), and (iii) high bond dissociation energy (BDE) of the C–N bonds in the anion state. Moreover, we conducted multiscale simulations to improve the hole-mobility ( μ h ). Consequently, the simulation suggested that permanent-dipole-induced site energy and reorganization energy are critical factors for improving μ h among HPB derivatives.